Evaluating the impact of lipids in isolated islet research - Jentz, Emelien M.; Joseph, Jamie W. (Frontiers in Endocrinology, 2025)
Pancreatic β-cells secrete insulin in response to nutrient stimulation. Glucose, amino acids and free fatty acids (FFA) have all been shown to stimulate insulin release in vivo. In vitro, isolated islet studies have also demonstrated similar results to those seen in vivo. It has also been shown that high-fat diet-fed mice or chronic treatment of isolated islets to high glucose and FFA can lead to glucolipotoxicity and impaired β-cell function. Isolated islet studies are a standard assay for preliminary testing of novel ideas and drugs related to islet function. Interpreting and comparing in vitro islet results from acute and chronic treatment of nutrients can be difficult since a wide variety of methods are used to isolate and culture islets and assess islet function. In this review, we compare in vivo and in vitro FFA absorption, transport and metabolism and discuss in vitro methods and concepts related to islet responses to nutrients, focusing on the effects of fatty acids on insulin secretion and β-cell function. This review also discusses FFA levels and transport seen in type 2 diabetes and compares them to how isolated islets are treated with FFA in vitro.